Withdrawal: Asymmetric Alkenyl Catellani Reaction for the Construction of C−N Axial Chirality. Issue 32 (26th July 2021) - Wu, Chenggui; Liu, Ze‐Shui; Shang, Yong; Liu, Chang; Deng, Shuang; Cheng, Hong‐Gang; Cong, Hengjiang; Jiao, Yinchun; Zhou, Qianghui
Abstract : The Accepted Article version of the above article, published online on 25 May 2021 in Wiley Online Library (wileyonlinelibrary.com), has been withdrawn by agreement between the corresponding author, the journal′s Executive Committee, and Wiley‐VCH GmbH, Weinheim. The withdrawal has been agreed upon due to significant conceptual similarities with another of the authors' recently published articles, which was not disclosed during the peer review process.